(untitled) (Международный научный журнал «Инженер», 2026)
The article covers issues related to the description of modern aspects of improving the efficiency and safety of train traffic, improving the quality of transport services for passengers and shippers, as well as contributing to the economic development of the region through the implementation of comprehensive modernization at stations and railway sections. The introduction of intelligent monitoring and diagnostic systems for rolling stock is recommended. It has been established that the introduction of automated control systems implies a significant reduction in the cost of train traffic management. It has been established that the introduction of intelligent systems for monitoring and diagnosing the condition of the track using sensors and artificial intelligence (AI) is also an important area in the development of track facilities. As a result, the successful development of railway transport requires a holistic approach that includes increasing investment attractiveness, introducing modern technologies, and taking into account the social needs of users.